Evaluation of the Quality of Financial Statements and Their Implications for Corporate Tax Reporting at CV Maha Karya Teknik - Setiani, Imelda Febi Ayu; Ardiansyah, Ardiansyah (Jurnal Ekualisasi, 2026)
Financial statements have a very crucial role as the main basis in the preparation and submission of tax statements, so their quality directly has implications for the level of compliance and transparency of the company's taxation. The authenticity of this research lies in the evaluation of the quality of financial statements as the foundation of tax reporting through the analysis of transaction recording systems and tax practices in medium-scale companies. This study aims to assess the extent to which the quality of financial statements serves as a reliable basis in tax reporting. The research uses a qualitative approach by collecting data through the analysis of financial statements for the period January 1 to December 31, 2024 as well as interviews with five informants who are directly involved in the tax reporting process, ranging from directors to administrative staff, with Tax Compliance Theory as the framework of analysis. The results of the study show that the company has implemented transaction recording and tax reporting quite well, although there is still a need to improve the reporting mechanism to be more systematic and in line with tax provisions. These findings have implications for the need to strengthen the quality of financial statements and transaction recording systems to improve tax compliance, minimize the risk of sanctions, and strengthen the company's credibility before tax authorities.